Characteristics and Prognostic Factors of Non-HIV Immunocompromised Patients With Pneumocystis Pneumonia Diagnosed by Metagenomics Next-Generation Sequencing - Duan, Jiali; Gao, Jing; Liu, Qiuhong; Sun, Mengfei; Liu, Yang; Tan, Yingshuai; Xing, Lihua (Frontiers in Medicine, 2022)
Objective The aim of this study was to evaluate the potential of metagenomic next-generation sequencing (mNGS) for the diagnosis of pneumocystis pneumonia (PCP) in patients with non-human immunodeficiency virus-infection and to discuss the clinical characteristics and identify prognostic factors associated with patients with non-HIV PCP. Methods Forty-six patients with PCP who were admitted in respiratory intensive care unit (ICU) between May 2018 and May 2020 were retrospectively reviewed. The subjects were divided into survivor and non-survivor groups according to the patients' outcome. Conventional methods and mNGS for detecting Pneumocystis jirovecii (P. jirovecii) were analyzed. The patients' demographics, comorbidities, laboratory parameters, and treatments were compared and evaluated in both groups to identify risk factors for mortality by using univariate and multivariate logistic regression. Results Metagenomic next-generation sequencing (mNGS) showed a satisfying diagnostic performance of 100% positive of detecting P. jirovecii from bronchoalveolar lavage (BAL) specimens in forty-six patients with non-HIV PCP, compared to only 15.2% for Gomori Methenamine silver (GMS) staining and 84.8% for Serum 1,3-beta-D-glucan (BDG). Among them, the mean age was 46.4-year-old (range 18–79-year-old) and mortality rate was 43.5%. The dominant underlying conditions were connective tissue diseases (34.8%), autoimmune kidney diseases (30.4%), followed by hematologic malignancies (10.9%), and solid organ transplantation (6.5%). A total of 38 cases (82.6%) received glucocorticoid and 19 cases (41.3%) used immunosuppressant within 3 months before diagnosed PCP. Multiple infections were very common, over two thirds' cases had mixed infections. Compared with survivors, non-survivors had a higher acute physiology and chronic health evaluation II (APACHE II) score (14.4 ± 4.8 vs. 10 ± 3.4), Procalcitonin (PCT) [ng/ml: 0.737 (0.122–1.6) vs. 0.23 (0.095–0.35)], lactic dehydrogenase (LDH) [U/L: 1372 (825.5–2150) vs. 739 (490.5–956)], and neutrophil-lymphocyte ratio (NLR) [21.6 (15.67–38.2) vs. 11.75 (5.1–15.52)], but had a lower PaO2/FiO2 ratio (mmHg:108.8 ± 42.4 vs. 150.5 ± 47.5), lymphocytes [×109/L: 0.33 (0.135–0.615) vs. 0.69 (0.325–1.07)] and CD4+ T cells [cell/μl: 112 (53.5–264) vs. 255 (145–303.5)], all P < 0.05. Furthermore, we found non-survivors' PaO2/FiO2 ratio of day 3 and day 7 had not improved when compared with that of day one, and platelet level and NLR became worse. Multivariate analysis showed that other pathogens' co-infection (OR = 9.011, 95% CI was 1.052–77.161, P = 0.045) and NLR (OR = 1.283, 95% CI was 1.046–1.547, P = 0.017) were the independent risk factors of poor prognosis. Conclusion mNGS is a very sensitive diagnostic tool for identifying P. jirovecii in patients who are non-HIV immunocompromised. PCP in patients who are non-HIV infected is associated with a high rate of multiple infections and severe condition. Mixed infection and elevation of NLR were the independent risk factors of poor prognosis.